Job Satisfaction and Turnover Intention: Moderation of Organizational Trust and Organizational Justice - Nurhayati, Mafizatun; Haningsih, Luna; Awaliyah, Syifa (KINERJA, 2020)
This study aims to analyze the role of organizational trust and organizational justice in moderating the effect of job satisfaction on turnover intention. The population in this study are employees in several information technology companies in Jakarta. The research sample amounts to 195 respondents. Data collection method is done through a questionnaire. Data analysis method uses structural equation modeling-partial least square (SEM-PLS). The results of this study prove that job satisfaction a negative affect on turnover intention. Organizational trust does not affect turnover intention. The interaction of job satisfaction and organizational trust as a moderating variable affects turnover intention. Organizational justice has a negative effect on turnover intention. The interaction of job satisfaction and organizational justice as a moderating variable does not affect turnover intention.Â